2015
DOI: 10.2147/ahmt.s76511
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between insomnia symptoms, aggressive behavior, and suicidality in adolescents?

Abstract: PurposeSleep disturbances are a common problem during adolescence. Often there is a relationship with the mental health of the affected person. The existing literature concerning the link between sleep disturbances and aggressive behavior and sleep disturbances and suicidality during adolescence shows no clear results. The present study tested a mediation model to prove the relation between sleep problems, aggressive behavior, and suicidality during adolescence. To take the link between suicidality and depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…19 This relationship between sleep problems and suicidality persisted when taking aggressive behavior and depression into account. 20 Correspondingly, nightmares were significantly related to suicidal ideation even after controlling for depression, anxiety and posttraumatic stress disorder. 21 Students who suffered from nightmares often reported more insomnia symptoms and lower self-efficacy.…”
Section: Introductionmentioning
confidence: 90%
“…19 This relationship between sleep problems and suicidality persisted when taking aggressive behavior and depression into account. 20 Correspondingly, nightmares were significantly related to suicidal ideation even after controlling for depression, anxiety and posttraumatic stress disorder. 21 Students who suffered from nightmares often reported more insomnia symptoms and lower self-efficacy.…”
Section: Introductionmentioning
confidence: 90%
“…However, most studies report a significant link between nightmares and either suicidal thoughts as measured by questionnaires or suicide attempts. In addition to nightmares, disturbed sleep in general and insomnia in particular increase the risk for suicidality 13 14 15 16 17 18 19 20 .…”
mentioning
confidence: 99%
“…In our study, nightmares played a prominent role based on self-report as well as regarding mediation. As previous studies reported, the occurrence of nightmares has a negative impact on daily wellbeing in regard to cognitive, emotional, motivational, as well as physiological aspects [20,73,77]. Moreover, nightmares come along with inferior school performance and further sleep problems (i.e., poor sleep quality, prolonged sleep latency) [12,78].…”
Section: Discussionmentioning
confidence: 95%
“…Sleep problems in youths tend to become chronic with the risk of reaching into adulthood [13][14][15][16][17]. Daytime impairments of sleep disturbances in adolescence vary from academic impairments and impaired quality of life to behavioral concerns such as aggression, depression, and suicidality [17][18][19][20]. On the other hand, sleep disturbances in adolescents have found to be correlated with fatigue, somatic symptoms such as headache, abdominal pain, backache, and poor health in general [12,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%